P664 The impact of vedolizumab on extra-intestinal manifestations in inflammatory bowel disease patients: A real-life experience of a single-centre cohort. (15th January 2020) - TRUYENS, M; Geldof, J; Dewitte, G; Glorieus, E; Varkas, G; Elewaut, D; Lobaton Ortega, T
Abstract: Background: Vedolizumab (VDZ), a gut-specific anti-integrin, is approved as a treatment for moderate to severe Crohn's disease (CD) and ulcerative colitis (UC). Extra-intestinal manifestations (EIMs) are frequently associated with inflammatory bowel disease (IBD). However, the effect of VDZ on EIMs remains unknown. The aim of the current study was to describe the prevalence of EIMs in IBD patients at VDZ initiation, the evolution during continued treatment as well as the occurrence of new EIMs. Methods: A single-centre study was performed in IBD patients who were started on VDZ between May 2010 and February 2019. Retrospectively, the physician-reported EIMs and intestinal disease activity (clinical and endoscopic) were assessed at baseline, 6 months and 1 year after the start of VDZ. Results: The cohort consisted of 134 patients, including 77 CD patients, 56 UC patients and 1 patient with unclassified IBD. At VDZ initiation EIMs were assessed in 127 patients and 17.3% had ≥ 1 EIM: 9 hepatic EIMs (2 patients with toxic hepatitis, 2 with autoimmune hepatitis and 5 with PSC), 7 arthropathies (6 patients with axial spondyloarthropathy and 1 with peripheral arthritis), 3 non-further specified axial or peripheral arthralgias and 3 cutaneous EIMs (urticaria, psoriasis and erythema nodosum). Clinical evolution of the EIMs is reported in Table 1, assessment of intestinal disease activity in Table 2. During follow-up, 23 new EIMs were seen, mainly arthralgia, which was often transient. VDZ was stopped in 39/130 (30%) patients due to active intestinal disease in 32 patients, patients' choice ( n = 1) or because of deep disease remission ( n = 1). In five patients, VDZ was stopped because of insufficient control of EIM. Conclusion: A good clinical intestinal response was observed. However, the clinical evolution of EIMs appears unaffected by the use of VDZ in our cohort. Prospective data are needed to confirm these results.